Microsoft Encarta encyclopedia deluxe 2000 - Microsoft Corporation ([Redmond, Wash.] Microsoft Corp., 1999)
Includes over 40,000 articles, 16,000 photos and illustrations, video clips and 3-D animations, sound clips, World Wide Web links, monthly yearbook and web link updates, multimedia collages, panoramic, 360-degree views, article sidebars, virtual tours, interactivities, and a research organizer.
Title from disk surface.
Installation and resources on individual CD-ROM.
System requirements: Multimedia PC with a Pentium or higher processor; Windows 95 or 98 or Windows NT 4.0 or later ; 16MB RAM (for Windows 95/98); 24MB RAM (for Windows NT Workstation); 48MB of available hard-disk space; 4X CD-ROM drive or faster; SVGA, 256-color monitor supporting 640x480 or higher resolution, 800x600 resolution recommended; local bus video with 1MB or more of video memory; Microsoft mouse, Microsoft IntelliMouse, or compatible pointing device; 16-bit sound card with speakers or headphones.
Encarta Research Organizer requires: 6MB of additional hard-disk space.
Encarta Yearbook, Web Links, and monthly online updates require: 14.4 or higher-baud modem ((28.8 or higher recommended); access to the Internet and World Wide Web, with browser; 2MB of additional hard-disk space for each monthly installment.
Microsoft Natural Language enhanced search capabilities require: 60MB of additional available hard-disk space.
Keywords: Electronic encyclopedias